Spēles metodes izmantošana skolēna izziņas darbības attīstīšanai dabaszinībās 1.-4.klasēs. - Pētersone, Sandra (Latvijas Universitāte, 2006)
Šajā diplomdarbā ir izpētītas spēles izmantošanas iespējas sākumskolā un izstrādātas spēles skolēnu izziņas darbības attīstīšanai dabaszinībās 2. klasei, kuras ir aprobētas Lielvārdes pamatskolas 2.a klasē. Darbā ir aplūkots, kā sākumskolas skolotāji vērtē spēļu metodes izmantošanu mācību stundās. Diplomdarba pielikumā ir izstrādātās spēles skolēnu izziņas darbības attīstīšanai dabaszinībās 2. klasē. Diplomdarba apjoms ir 54 lpp., tai skaitā 8 diagrammas.

The abilities of using games are studied in this diploma work as well as games for development of pupil’s activity of cognition in science for grade 2, that is approbated in Lielvarde Primary school, excatly form 2a. Here is looked over how teachers in elementary school estimate using methods of games during the lessons, as well. In appendix of this diploma work there are games worked out for development of activity of cognition in science in form 2. Amount of the work is 54 pages, including 8 charts.
Use of games for developing pupils’ cognitive activity in nature sciences lessons in Grades 1 - 4.
Keywords: Pedagoģija